CLEAN INDOOR AIR COALITION ORGANIZATIONAL OUTLINE (Tufts Archival Research Center, 2007)
Memorandum from Peter Sparber to Paul Cammer and Bruce Dickson regarding the proposed Indoor Air Coalition. States the purpose of the organization is to make public policy in the issue of clean indoor air. Lists structure and governance, membership, finance, functions and timeline.